CALCIUM REQUIREMENT IN RELATION TO MILK FEVER FOR HIGH YIELDING DAIRY COWS: A REVIEW - Angassa TESFAYE (Stefan cel Mare University of Suceava, 2019)
The purpose of this paper is to review the predisposing factors and advances in controlling principles of milk fever in high yielding dairy cows. Dietary imbalances in dairy cows can be one of fundamental cause of numerous and complicated types of health problems that are usually categorized as metabolic disorders. High producing dairy cows are among highly susceptible animal to such metabolic disorders during their transitional periods; three weeks before and after calving. In these periods, the animal struggles to maintain their calcium homeostasis; which is the most common metabolic disorder of high yielding dairy cows, due to their underlying physiological and pathological factors. Thus, those factors predisposing dairy cows to milk fever are age, stage of lactation and parity, body condition and diet. Usually, the basic principle of controlling milk fever is feeding the cows from diet constituting lower calcium and potassium contents in dry period. So that calcium mobilization from bone would be promoted, which ensures the increased metabolic processes of calcium mobilization during the transition period? Furthermore, supplementations of various anionic salts which includes magnesium sulfate, calcium sulfate, ammonium sulfate, calcium chloride, ammonium chloride and magnesium chloride are commonly used to raise blood calcium level, thus, minimizes risks of milk fever. Also, body condition management of cows during dry period is used to prevent milk fever. Finally, a recent research indicates that serotonin intravenous injections have significantly reduced the incidence of hypocalcemia in high yielding dairy cows.